2020
DOI: 10.1097/qad.0000000000002463
|View full text |Cite
|
Sign up to set email alerts
|

Week 96 results of a phase 3 trial of darunavir/cobicistat/emtricitabine/tenofovir alafenamide in treatment-naive HIV-1 patients

Abstract: Background: Darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg was investigated through 96 weeks in AMBER (NCT02431247). Methods: Treatment-naive, HIV-1-positive adults [screening plasma viral load ≥1000 copies/ml; CD4+ cell count >50 cells/μl) were randomized (1 : 1) to D/C/F/TAF (N = 362) or D/C plus emtricitabine/tenofovir-disoproxil-fumarate (F/TDF) (N = 363) over at least 48 weeks. After week 48, patients coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…These clinical trials were conducted over more than a 10-year span, providing 5291 patientyears of experience with this regimen. 20,21,23,30 A limitation of the analysis is that the studies did not include integrase inhibitor-based regimens, which were not available at the time that some of the studies in this analysis took place. Additionally, the analysis reported here only includes data from controlled clinical trials and does not include real-world data.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These clinical trials were conducted over more than a 10-year span, providing 5291 patientyears of experience with this regimen. 20,21,23,30 A limitation of the analysis is that the studies did not include integrase inhibitor-based regimens, which were not available at the time that some of the studies in this analysis took place. Additionally, the analysis reported here only includes data from controlled clinical trials and does not include real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological details for the seven clinical studies included in the previous analysis have been described. 6,[10][11][12][13][14][15][16] Detailed methods for the three recent studies of the D/C/F/TAF STR have also been reported [19][20][21][22][23] and are briefly summarized here. Key study design information for all 10 studies is shown in Supplemental Figure S1.…”
Section: Study Designsmentioning
confidence: 99%
See 3 more Smart Citations